Nanocomposite containing CaF2 nanoparticles: Thermal cycling, wear and long-term water-aging - Weir, Michael D.; Moreau, Jennifer L.; Levine, Eric D.; Strassler, Howard E.; Chow, Laurence C.; Xu, Hockin H.K. (Dental materials, 2012)
Fluoride (F) releasing dental restoratives are promising to promote remineralization and combat caries. The objectives of this study were to develop nanocomposite containing calcium fluoride nanoparticles (nCaF2), and to investigate the long-term mechanical durability including wear, thermal-cycling and long-term water-aging behavior. Two types of fillers were used: nCaF2 with a diameter of 53nm, and glass particles of 1.4μm. Four composites were fabricated with fillers of: (1) 0% nCaF2+65% glass; (2) 10% nCaF2+55% glass; (3) 20% nCaF2+45% glass; (4) 30% nCaF2+35% glass. Three commercial materials were also tested. Specimens were subjected to thermal-cycling between 5°C and 60°C for 105 cycles, three-body wear for 4×105 cycles, and water-aging for 2 years. After thermal-cycling, the nCaF2 nanocomposites had flexural strengths in the range of 100–150MPa, five times higher than the 20–30MPa for resin-modified glass ionomer (RMGI). The wear scar depth showed an increasing trend with increasing nCaF2 filler level. Wear of nCaF2 nanocomposites was within the range of wear for commercial controls. Water-aging decreased the strength of all materials. At 2 years, flexural strength was 94MPa for nanocomposite with 10% nCaF2, 60MPa with 20% nCaF2, and 48MPa with 30% nCaF2. They are 3–6 fold higher than the 15MPa for RMGI (p<0.05). SEM revealed air bubbles and cracks in a RMGI, while composite control and nCaF2 nanocomposites appeared dense and solid. Combining nCaF2 with glass particles yielded nanocomposites with long-term mechanical properties that were comparable to those of a commercial composite with little F release, and much better than those of RMGI controls. These strong long-term properties, together with their F release being comparable to RMGI as previously reported, indicate that the nCaF2 nanocomposites are promising for load-bearing and caries-inhibiting restorations.